2019
DOI: 10.1186/s12943-019-1065-4
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-mediated N6-methyladenosine modification is critical for epithelial-mesenchymal transition and metastasis of gastric cancer

Abstract: Background As one of the most frequent chemical modifications in eukaryotic mRNAs, N6-methyladenosine (m6A) modification exerts important effects on mRNA stability, splicing, and translation. Recently, the regulatory role of m6A in tumorigenesis has been increasingly recognized. However, dysregulation of m6A and its functions in tumor epithelial-mesenchymal transition (EMT) and metastasis remain obscure. Methods qRT-PCR and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
373
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(389 citation statements)
references
References 48 publications
15
373
0
1
Order By: Relevance
“…METTL3 and m 6 A were upregulated in human osteosarcoma (46), gastric cancer (23,47,48), melanoma (49), ovarian carcinoma (50), and hepatocellular carcinoma (51). Its expression level gradually increased with the increasing tumor stage and grade.…”
Section: Mettl3 In Other Cancersmentioning
confidence: 95%
See 1 more Smart Citation
“…METTL3 and m 6 A were upregulated in human osteosarcoma (46), gastric cancer (23,47,48), melanoma (49), ovarian carcinoma (50), and hepatocellular carcinoma (51). Its expression level gradually increased with the increasing tumor stage and grade.…”
Section: Mettl3 In Other Cancersmentioning
confidence: 95%
“…Its expression level gradually increased with the increasing tumor stage and grade. METTL3 was an indicator of poor prognosis and METTL3 silencing inhibited the proliferation, migration, and invasion abilities of cells, colony formation, and motility (24,(47)(48)(49)(50)(51)(52), demonstrating that METTL3 plays an oncogenic role in these cancers. Taketo et al reported that a METTL3-knockdown pancreatic cancer cell line showed higher sensitivity to anticancer agents such as gemcitabine, 5-fluorouracil, cisplatin, and irradiation, suggesting that METTL3 is a potential target for the enhancement of therapeutic efficacy (25).…”
Section: Mettl3 In Other Cancersmentioning
confidence: 99%
“…Loss of METTL3 results in higher level of BCL-XS isoform and NCOR2α isoform and inhibition of GSC growth and self-renewal [41]. In gastric cancer, upregulated METTL3 promotes stability of ZMYM1, thus enhancing EMT process in vitro and metastasis in vivo [42]. Moreover, METTL3 can also participate in regulation of target mRNA in a post-modification way, therefore partially acting as a reader [43,44].…”
Section: Mettl3mentioning
confidence: 99%
“…Firstly, a few of non-classic m 6 A readers are found through RNA sequencing, such as HuR and SND1. ZMYM1 mRNA, which could facilitate the process of EMT and the metastasis of GC, was modified by m 6 A and its stability was enhanced relying on the recognition by HuR [116]. Another novel m 6 A reader SND1 bound to the m 6 A sites of ORF50 transcript and promoted its stability.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Increasing the expression of β-catenin, WNT6 and FZD9A to activate Wnt/β-catenin pathway [49] YTHDF3 GAS5 Enhancing the degradation of lncRNA GAS5 [50] YTHDC1 circNSUN2 Facilitating circNSUN2 export from nucleus to cytoplasm [51] IGF2BP2 HMGA2 Forming a circNSUN2/IGF2BP2 complex to fortify the stability of HMGA2 [51] IGF2BP2 SOX2 Stabilizing SOX2 mRNA [52] Gastric cancer IGF2BP1 SEC62 Augmenting SEC62 mRNA translation [53] IGF2BP3 HDGF Facilitating HDGF mRNA expression [54] HuR ZMYM1 Fortifying the stability of ZMYM1 mRNA [116] Lung cancer YTHDF1 CDK2, CDK4, cyclinD1…”
Section: Conclusion and Perspectivementioning
confidence: 99%